The risk status, signatures of adaptation, and environmental suitability of village-based indigenous chickens from certain regions of Limpopo and KwaZulu-Natal provinces of South Africa - Mogano, Reneilwe Rose; Mpofu, Takalani Judas; Mtileni, Bohani; Hadebe, Khanyisile (Frontiers in Genetics, 2024)
Indigenous chickens are an important Farm Animal Genetic Resource (FAnGR) in South Africa as they alleviate poverty and are a source of protein. Climate change and market demand for high-performing exotic breeds threaten and undermine locally adapted village chickens. The current study explored the risk status and signatures of adaptation of village-based indigenous chickens from two provinces and mapped their environmental suitability across the country. A total of 244 village chickens from rural areas of the Capricorn (n = 85) and Sekhukhune (n = 113) districts of Limpopo province; the Harry Gwala (n = 21) and uMzinyathi (n = 25) districts of KwaZulu-Natal province were genotyped using the Illumina 60K BeadChip. The conservation flock comprised Ovambo (OV; n = 10), Potchefstroom KoeKoek (PK; n = 20), and Venda (VD; n = 20). Naked Neck (NN; n = 20), New Hampshire (NH; n = 10), White Leghorn (WL; n = 10), and White Plymouth Rock (WR; n = 10) from the Agricultural Research Council Poultry Breeding Unit were used as reference populations and representative of flocks under conservation. The effective population size (Ne) in village chickens and conserved flocks ranged from 18 to 53 and 26 to 38 at 12 generations ago, respectively. PC1 and PC2 explained 5.64% of the total variation, which resulted in five clusters with the Venda, Naked Neck, and White Leghorn being separated from village chickens. The first three redundancy analysis (RDA) axes capture 46.8% of the total genetic variation used to detect significant outlier SNPs. A total of 386 outlier SNPs associated with all 10 environmental variables were detected. Using ecological niche modeling, chickens from Dipakakeng, Mgababa, and Podu villages, Limpopo, had a localized predicted suitability probability, while chickens originating from Nhlonga village, KwaZulu-Natal, had a broader distribution of predicted suitability habitats with elevation and BIO6 being important variables. The results of this study provide insight into the risk status, geographic suitability, and contributing environmental factors of indigenous chickens that can be used to influence conservation and improvement decisions.